Simian Virus 40 Activates ATR-Δp53 Signaling To Override Cell Cycle and DNA Replication Control - Rohaly, Gabor (American Society for Microbiology (ASM), 2010)
During infection, simian virus 40 (SV40) attempts to take hold of the cell, while the host responds with various defense systems, including the ataxia-telangiectasia mutated/ATM-Rad3 related (ATM/ATR)-mediated DNA damage response pathways. Here we show that upon viral infection, ATR directly activates the p53 isoform Δp53, leading to upregulation of the Cdk inhibitor p21 and downregulation of cyclin A-Cdk2/1 (AK) activity, which force the host to stay in the replicative S phase. Moreover, downregulation of AK activity is a prerequisite for the generation of hypophosphorylated, origin-competent DNA polymerase α-primase (hypo-Polα), which is, unlike AK-phosphorylated Polα (P-Polα), recruited by SV40 large T antigen (T-Ag) to initiate viral DNA replication. Prevention of the downregulation of AK activity by inactivation of ATR-Δp53-p21 signaling significantly reduced the T-Ag-interacting hypo-Polα population and, accordingly, SV40 replication efficiency. Moreover, the ATR-Δp53 pathway facilitates the proteasomal degradation of the 180-kDa catalytic subunit of the non-T-Ag-interacting P-Polα, giving rise to T-Ag-interacting hypo-Polα. Thus, the purpose of activating the ATR-Δp53-p21-mediated intra-S checkpoint is to maintain the host in S phase, an optimal environment for SV40 replication, and to modulate the host DNA replicase, which is indispensable for viral amplification.